Rethinking African in the Global Development Agenda: Pathway to Economic Transformation - Okeowo, Idowu Adeniyi; Adewale, Amos Segun; Onodingene, Herbert (Yayasan Sinergi Kawula Muda, 2025)
This research is motivated by the urgent need to rethinking Africa’s development within the global space. Rethinking Africa’s development must transcend isolated national efforts and emerge as a coordinated continental imperative. Repositioning Africa within the global development architecture necessitates coordinated strategies from regional institutions. The research used time series data from 1990-2024. Having observed the data properties, that all the data series are non-stationary at levels but stationary at first difference using Augmented Dickey-Fuller (ADF), and all the variables are cointegrated using Hansen Test of Co-integration, Fully Modified Ordinary Least Square (FMOLS) is used in the study. The results shows that a 19.4-unit increase in FDI corresponds to a one-unit increase in GDP, demonstrating that FDI significantly contributes to economic growth in Africa. Aligned with established economic literature, the results further indicate that increases in GDP lead to reductions in Africa’s poverty rates. Furthermore, the analysis reveals a positive association between the Human Development Index (HDI) and GDP, indicating that improved human capital positively influences economic output in Africa. it was recommended that Trade expansion, export promotion, and enhanced regional integration must be central to Africa’s economic agenda. Increasing GDP should not be Africa’s sole objective. Equally critical is the enhancement of key macroeconomic indicators, including human capital development. Addressing unemployment, poverty, inequality, and improving the quality of education and healthcare systems are essential for increasing productivity and positioning Africa competitively within the global economy.